Tacit knowledge: the explanatory study of the impact of ppsmi towards English fluency among university students / Mohd Zool Hilmie Mohamed Sawal...[et al.] - Mohamed Sawal, Mohd Zool Hilmie; Azmi, Nor Azlina; Noordin, Nazni; Zakaria, Zaherawati (2010)
Malaysian’s former prime minister, Tun Dr. Mahathir bin Mohamad introduced Pengajaran dan Pembelajaran Sains dan Matematik dalam Bahasa Inggeris (PPSMI) in 2003. It is a Malaysian Government policy aiming towards primary and secondary schools in Malaysia with the purpose to improve English fluency among Malaysian pupils. In this policy, Science and Mathematics subject will be fully thought in English instead of the previous Bahasa Melayu. This paper tries to explore the impact of PPSMI towards tacit knowledge among university students to determine the effectiveness of this program whether or not it helps these students with their higher learning pursue in local and private universities among which writing skills, presentation skills, text book comprehensiveness including class discussion period were involved.